Study of Economical-Technical Impacts of Distributed Generation on Medium-Voltage Grid - Thi Dieu Thuy Nguyen; Jiangjun Ruan; Quan Nhu Nguyen; Ngoc Giang Le; Dan Tan; Longfei Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The development of Science and Technology has spurred the development of distributed generation, as well as the application of new renewable energy sources. DG connected to the grid can alter the power flow on the grid, reduce voltage loss and grid capacity loss; and also enhance the incident and reliability of grid power supply. When the number of DG connected to the grid increases, capacity direction varies depending on the distribution and consumption at specific time. Consequently, capacity losses in the grid can be reduced. Besides, DG connected to the grid is closely linked to the matters of environmental pollution and degradation, economic growth and living standard. This paper will discuss the impacts of grid-distributed generation on economic and technical indicators, which mainly focus on the relationship between degree of penetration and location of DG connection to the grid, regarding voltage and capacity losses in the line. The proposed model is calculated and tested via a 56-bus radial distribution system in the DELPHI7 programming language. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3796